The effect of caffeine consumption on attention performance in female students at the faculty of health sciences - AGOPYAN, ANİ (My University, 2022)
Purpose There are limited studies on the effects of coffee consumption, which has become part of popular culture and is highly common among young people, on the attention levels of female university students. This paper aims to examine the effects of caffeine consumption given at different doses (0, 100 and 200 mg) to female university students (n = 100) studying at the faculty of health sciences on attention performance with the Stroop Color and Word Test (SCWT). Design/methodology/approach Participants\" test completion time, number of errors and corrections were tested. In addition, the frequencies of weekly coffee consumption were also recorded. Findings It was found that consumption of coffee containing 200 mg of caffeine reduced the time to complete the sections of the SCWT test (p < 0.05), as well as the total test completion time (55.81 +/- 8.67 s) compared to no coffee consumption (58.25 +/- 9.46 s) and coffee consumption with 100-mg caffeine (57.56 +/- 8.87 s) (p < 0.05; effect size: 0.268). The effect of caffeine on attention level was induced by 200-mg caffeine consumption, but was unapparent at 100-mg dose. In addition, SCWT completion times were reduced in the student group with more weekly coffee consumption (=3 cups/week) at 200-mg caffeine dose. Originality/value In this context, caffeine dose is a factor that should be taken into account in determining the performance of individuals in the SCWT test. It is thought that coffee consumption can increase the concentration of students and have positive effects on academic achievement.
Keywords: Tarımsal Bilimler; Ziraat; Gıda Mühendisliği; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Food Engineering; Engineering and Technology; GIDA BİLİMİ VE TEKNOLOJİSİ; Tarım Bilimleri; Tarım ve Çevre Bilimleri (AGE); FOOD SCIENCE & TECHNOLOGY; AGRICULTURAL SCIENCES; Agriculture & Environment Sciences (AGE); Yemek bilimi; Yaşam Bilimleri; Food Science; Life Sciences; Coffee; Caffeine; Focus; Attention; Stroop test; DOUBLE-BLIND; STROOP TASK; COFFEE; RESPONSES; MOOD